(untitled) (Global Journals of Research in Engineering, 2023)
Spintronics is an interactive combination of electronics and magnetics that has grown in popularity in the twenty-first century as nanotechnology has advanced Spintronics is a new type of electronics that employs mutual control of magnetic and other physical signals such as electrical and optical signals Spin current has recently received a lot of attention as a basic idea in spintronics Understanding spin current entails deciphering the mechanisms underlying the mutual control of diverse physical signals which should lead to future advances in spintronics The notion of spin current and its historical context are discussed first in this chapter followed by a discussion of innovative materials for spintronics Much attention is also dedicated to the physical phenomena that result from the coupling of spins